1963
DOI: 10.1152/ajplegacy.1963.205.5.905
|View full text |Cite
|
Sign up to set email alerts
|

Acetate-1-C14 metabolism of white fat from hamsters in cold exposure and hibernation

Abstract: Incorporation of C14 from acetate-1-C14 into lipid and CO2 by epididymal fat from golden hamsters kept at room temperature, acclimated to 5 ± 1 C, in hibernation and arousing from hibernation, was measured in vitro at 37 C. Summer and winter series were compared. The C14O2 production by tissue from control and acclimated animals was similar but the C14O2 production of tissue from hibernating and arousing hamsters was significantly greater than that from acclimated animals. There was a large increase in the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The up-regulation of Gpam , a rate-limiting enzyme of triglyceride synthesis, may prevent over-shrinkage of white adipocytes and limit lipodystrophy by promoting lipogenesis before the onset of hibernation and during HIB. The simultaneous induction of lipid catabolism and anabolism genes in iWAT may be a phenotype that is unique to hamster hibernation (Baumber and Denyes, 1963); Syrian hamsters do not fatten during the pre-HIB under SD-Cold, and reduce their body mass below approximately 140 g (Chayama et al, 2016). They hoard food before the onset of hibernation (Larkin et al, 2002), and during PA states they do ingest small amounts of food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The up-regulation of Gpam , a rate-limiting enzyme of triglyceride synthesis, may prevent over-shrinkage of white adipocytes and limit lipodystrophy by promoting lipogenesis before the onset of hibernation and during HIB. The simultaneous induction of lipid catabolism and anabolism genes in iWAT may be a phenotype that is unique to hamster hibernation (Baumber and Denyes, 1963); Syrian hamsters do not fatten during the pre-HIB under SD-Cold, and reduce their body mass below approximately 140 g (Chayama et al, 2016). They hoard food before the onset of hibernation (Larkin et al, 2002), and during PA states they do ingest small amounts of food.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the aforementioned fat-storing hibernators, Syrian (golden) hamsters ( Mesocricetus auratus ) are food-storing hibernators that eat food stored in the nest during PA. It was reported that they maintain a high lipogenic capacity of WAT in both Pre-HIB and HIB in response to prolonged cold (Baumber and Denyes, 1963). Despite this difference between fat-storing and food-storing hibernators, the above studies suggest that dynamic reorganization of lipid metabolic pathways is a key feature of pre-hibernation remodeling in mammalian hibernators examined so far, whereas it is yet unclear how the reorganization is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Prehibernation cold exposure in Syrian hamsters results in inhibition of lipogenesis in the liver (Denyes and Carter 1961) but a four-to sixfold increase in the in vitro capacity of lipogenesis from acetate in the white adipose tissue (Baumber and Denyes 1963). Further, this increased lipogenic capacity is retained during hibernation unlike the inhibition of lipogenic capacity with the onset of hibernation in ground squirrels and hedgehogs described above.…”
Section: Glucose Metabolismmentioning
confidence: 93%